2018
DOI: 10.1038/s41598-018-26574-3
|View full text |Cite
|
Sign up to set email alerts
|

Associations of passive muscle stiffness, muscle stretch tolerance, and muscle slack angle with range of motion: individual and sex differences

Abstract: Joint range of motion (ROM) is an important parameter for athletic performance and muscular injury risk. Nonetheless, a complete description of muscular factors influencing ROM among individuals and between men and women is lacking. We examined whether passive muscle stiffness (evaluated by angle-specific muscle shear modulus), tolerance to muscle stretch (evaluated by muscle shear modulus at end-ROM), and muscle slack angle of the triceps surae are associated with the individual variability and sex difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
86
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(96 citation statements)
references
References 41 publications
5
86
5
Order By: Relevance
“…The ROM is believed by practitioners to reflect muscle elasticity. However, it is well documented that the parameter can be strongly by the examiners' or examinees' subjectivity (including individual variability in stretch tolerance) [5,6]. Another approach to evaluate joint flexibility is to assess the slope of passive torque-joint angle curve, which is often used in laboratory experiments and referred to as joint stiffness.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ROM is believed by practitioners to reflect muscle elasticity. However, it is well documented that the parameter can be strongly by the examiners' or examinees' subjectivity (including individual variability in stretch tolerance) [5,6]. Another approach to evaluate joint flexibility is to assess the slope of passive torque-joint angle curve, which is often used in laboratory experiments and referred to as joint stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, ultrasound shear wave elastography (SWE) has been used to quantify tissue shear modulus (a measure of elasticity, expressed in kPa) independently of the influences of other anatomical structures, by measuring shear wave propagating speed [7,8]. Using this technique, some studies have examined associations between muscle elasticity (i. e., shear modulus) and joint flexibility (e. g., ROM and joint stiffness) in plantar flexors [6,9,10]. Others have quantified the shear modulus of individual muscles of the hamstring [11][12][13][14][15], which is the most frequently strained muscle group and one of the most studied muscles in terms of joint flexibility [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also shown no sex diŠerence in joint ROM and PT (Gajdosik et al, 2006;Morse, 2011). However, most previous studies have shown that joint ROM in women is greater than that in men (Cipriani et al, 2012;Davis et al, 2008;Marshall and Siegler, 2014;Miyamoto et al, 2018). In addition, the stiŠness of muscles, tendons and MTUs was greater in men (Blackburn et al, 2004;Kubo et al, 2003;Morse, 2011).…”
Section: Discussionmentioning
confidence: 88%
“…Some previous studies have suggested the involvement of estrogen, which aŠects collagen synthesis and tissue behavior (Burgess et al, 2009;Kjaer and Hansen, 2008;Morse, 2011). However, one recent study found no signiˆcant changes in ROM and muscle elasticity during the menstrual cycle (Miyamoto et al, 2018). Furthermore, sex diŠerences have been shown during menses, when estradiol levels are lowest (Hoge et al, 2010).…”
Section: Discussionmentioning
confidence: 99%